PENGARUH PENDIDIKAN KESEHATAN MELALUI MEDIA VIDEO ANIMASI TENTANG PENGETAHUAN BAHAYA SEKS PRANIKAH - Nanlohy, Sientya (STIKES Widyagama Husada, 2025)
Premarital sexual behavior is one of the adolescent problems that must be addressed immediately, one way is by providing health education through animated video media about the dangers of premarital sex. The use of animated videos in health education not only makes learning more fun, but can also increase adolescents' interest and attention to topics that may be considered taboo or boring. This study aims to examine the effect of health education through animation video media on adolescents' knowledge about the dangers of premarital sex. This research employed a quasi-experimental method with a pretest-posttest control group design. Samples were taken using simple random sampling techniques, with a total sample size of 36 respondents. Data analysis was performed using the Mann-Whitney Test. The knowledge of adolescents before being given health education through animated video media was mostly in the high category with 16 respondents and after being given health education through animated video media increased to the high category to 18 respondents with a p-value < 0.001. There is an effect of health education through animated video media on adolescents' knowledge about the dangers of premarital sex.